(untitled) (Research, Society and Development, 2022)
It was proposed to carry out with this study, a review of the literature regarding risk factors for gastric cancer. Data were collected through a literature review using the descriptors in science and health of CS/ MeSH: Gastric cancer, Helicobacter pylori, Risk factor, based on articles published through the scientific databases: Scielo, Lilacs, MedLine and Google Scholar, in addition to other sources such as INCA – Instituto Nacional de Câncer. A total of 27 scientific articles were collected, of which 8 met the exclusion criteria, leaving 14 works within the inclusion criteria. Gastric cancer affects many people worldwide, because with the advent of globalization, the lifestyle has changed, developing habits that are harmful to health and that enhance the chances of developing gastric cancer, in addition to intrinsic factors such as genetics. -relatives. Excessive consumption of meat is one of the factors that can lead to a malignant neoplasm, since substances released in its preparation can be carcinogenic. As well, helicobacter pylori is also linked to the pathogenesis of gastric cancer due to its ability to interact with host cells and the inflammatory response. In addition, genetic alterations can contribute to a possible malignant tumor, the inactivation of the P 53 gene, which is a tumor suppressor gene, for example. In general, environmental factors, as well as eating habits, smoking and genetic factors, are possible factors that can lead to gastric cancer.